Nexus between Technological Capabilities and Firm Performance: A Critical Review of the Literature and Research Agenda - Mukkorah, Grant; Kilika, James (European Journal of Business and Strategic Management, 2025)
Purpose: The technological capability of an organization plays a strategic role in enhancing the performance of organizations as it addresses strategic decisions that influence the deployment of economic resources in the value creation process to deliver goods and services. The purpose for the study was to conceptualize and review the already existing theoretical and empirical literature and methodological gaps and propose a conceptual model depicting the relationship between technological capability and firm performance for implementation. Methodology: Explore techniques employed to operationalize this concept and to make it relevant to beneficiaries and research participants who include; scholars, policy makers, organizational managers and the general public. The study reviews the pertinent theories, constructs and their operational indicators and compared against the existing empirical work and emergent knowledge gaps identified. Findings: The construct was found to have a place in strategic management as a strategy that can enhance a firm’s performance and competitive advantage. The study further highlighted the moderating role of the environment in governing the relationship between technological capabilities, firm competences and firm performance. The study further presented the conceptual understanding of all the constructs through identification of the operational indicators as well as the theoretical postulates anchoring each construct. Unique Contribution to Theory, Practice and Policy: The theories underpinning the study include the resource based view model and dynamic capabilities theory. Finally, the study proposes a multidisciplinary based theoretical model suitable for advancing knowledge in this area together with the accompanying implications for future research.